Biomechanical analyses of synchronised swimming standard and contra-standard sculling - Gomes, L. E.; Diogo, V.; Antônio de Souza Castro, F.; Vilas-Boas, J. P.; Fernandes, R. J.; Figueiredo, P. (Sports Biomechanics, 2019)
Synchronised swimming involves a variety of sculling movements essential for body support and propulsion but its study is scarce. We aimed to biomechanically compare standard and contra-standard sculling techniques, and to observe the relationship between measures. Six synchronised swimmers performed two, 30 s maximal intensity, fully tethered standard and contra-standard sculling motions. Kinetic and kinematic data were obtained using a load-cell and underwater cameras, respectively. Force decreased along both techniques` bouts, but no differences in-between techniques were noted for any kinetic variables. Standard sculling presented a higher cycle rate and a lower elbow mean angle than the contra-standard sculling (2.4 ± 0.3 vs. 2.0 ± 0.2 cycles/s and 134.1 ± 5.8 and 141.5 ± 4.7°, p < 0.05). In the standard sculling, by removing and maintaining the variation between participants (r w and r, respectively), the absolute mean force was directly related with cycle rate (r w = 0.60) and wrist angular velocity during flexion (r = 0.82), while in the contra-standard condition the force was inversely associated with wrist mean angle (r = -0.95) and directly with hand speed (r w = 0.76), and elbow angular velocity (r w ˜ 0.60). Therefore, technique learning and training require different attention by coaches and swimmers.